2013
DOI: 10.1128/aem.01031-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anaerobic Toluene Biodegradation Activity by bssA Transcript/Gene Ratios

Abstract: Benzylsuccinate synthase (bssA) genes associated with toluene degradation were profiled across a groundwater contaminant plume under nitrate-reducing conditions and were detected in significant numbers throughout the plume. However, differences between groundwater and core sediment samples suggested that microbial transport, rather than local activity, was the underlying cause of the high copy numbers within the downgradient plume. Both gene transcript and reactant concentrations were consistent with this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…As the catalytic activity of benzylsuccinate synthase is irreversibly destroyed by oxygen (51), its absence in the aerobic CW model makes sense; however, a surprise was that bssA transcripts were the highest of all quantified genes involved in toluene degradation. The presence of bssA transcripts without concomitant in situ anaerobic toluene degradation was previously observed (52). Basal expression of bssA was induced either by toluene or nitrate, which might explain the detection of bssA transcripts without protein translation in our system.…”
Section: Fig 3 Dynamics Of Different Protein Abundances During the DIsupporting
confidence: 77%
“…As the catalytic activity of benzylsuccinate synthase is irreversibly destroyed by oxygen (51), its absence in the aerobic CW model makes sense; however, a surprise was that bssA transcripts were the highest of all quantified genes involved in toluene degradation. The presence of bssA transcripts without concomitant in situ anaerobic toluene degradation was previously observed (52). Basal expression of bssA was induced either by toluene or nitrate, which might explain the detection of bssA transcripts without protein translation in our system.…”
Section: Fig 3 Dynamics Of Different Protein Abundances During the DIsupporting
confidence: 77%
“…A previous study determined that the expression of tceA or vcrA remained elevated for more than 48 h after the disappearance of TCE (12). A more recent study on expression of the benzylsuccinate synthase gene, bssA, identified a rapid decline of mRNA transcripts by over 2 orders of magnitude upon depletion of nitrate (56). However, similar to our study showing maintained expression levels of DXMO and ALDH, bssA transcripts stabilized and maintained greater than 1.0 ϫ 10 4 copies/ml for over 3 weeks after nitrate was removed (56).…”
Section: Discussionmentioning
confidence: 99%
“…Already, Kazy et al [2010] have indicated a significant correlation between anaerobic toluene degradation rates and qPCR bssA counts in anaerobic microcosms prepared with material from a hydrocarbon-contaminated aquifer. More recently, toluene degradation activity stimulated by the addition of nitrate was quantitatively monitored via bssA transcript-to-gene ratios across a contaminant plume directly in the field [Brow et al, 2013]. Both represent relevant advances towards the future implementation of a marker gene-or transcript-based prediction of biodegradation rates in complex natural systems.…”
Section: Discussionmentioning
confidence: 99%